ABNORMAL AQUAPORIN-3 PROTEIN EXPRESSION IN HYPERPROLIFERATIVE SKIN DISORDERS - Voss, Kristen E. (2011)
Non-melanoma skin cancers (NMSCs) and psoriasis represent common hyperproliferative skin disorders, with approximately one million new NMSC diagnoses each year in the United States alone and a psoriasis prevalence of about 2% worldwide. We recently demonstrated that the glycerol channel, aquaporin-3 (AQP3) and the enzyme phospholipase D2 (PLD2) interact functionally in epidermal keratinocytes of the skin to inhibit their proliferation. However, others have suggested that AQP3 is pro-proliferative in keratinocytes and is upregulated in the NMSC, squamous cell carcinoma (SCC). To evaluate the AQP3/PLD2 signaling module in skin diseases, we determined their levels in SCC, basal cell carcinoma (BCC) and psoriasis compared to normal epidermis. Skin biopsies with the appropriate diagnoses (ten normal, five SCC, thirteen BCC and ten plaque psoriasis samples) were obtained from the pathology archives and examined by immunohistochemistry using antibodies recognizing AQP3 and PLD2. In normal epidermis AQP3, an integral membrane protein, was localized mainly to the plasma membrane and PLD2 to the cell periphery, particularly in suprabasal layers. In BCC, AQP3 and PLD2 levels were reduced compared to the normal-appearing overlying epidermis. In SCC, AQP3 staining was “patchy,” with areas of reduced AQP3 immunoreactivity exhibiting positivity for Ki67, a marker of proliferation. PLD2 staining was unchanged in SCC. In psoriasis, AQP3 staining was usually observed in the cytoplasm rather than in the membrane. Also, in the majority of psoriatic samples, PLD2 showed weak immunoreactivity or aberrant localization. These results suggest that abnormalities in the AQP3/PLD2 signaling module correlate with hyperproliferation in psoriasis and the NMSCs.